Physico-chemical Conditions of the Surface Modification Process of Steels by Vanadium, Carbon and Nitrogen - N.A. Harchenko; V.G. Hignjak; Т.P. Hоvоrun; A.I. Degula (Журнал нано- та електронної фізики)
Theoretical calculations of the physical and chemical conditions of the nitrogenvanading process of steels are performed. The diagrams of the equilibrium composition of the reaction medium are presented. The phase composition of gaseous and condensed states of the systems, the optimum saturation temperature and mixture composition are derived. The optimal temperature range of nitrogenvanading of steels is established as follows: 1100-1300 K.